Pelaksanaan Layanan Bimbingan Kelompok Untuk Meningkatkan Disiplin Belajar Peserta Didik: Implementation Of Group Guiding Services To Improve Discipline Learning Students - Ana Puspita; Mohammad Fatchurahman (Suluh: Jurnal Bimbingan dan Konseling, 2018)
The purpose of this study to find out the development of content mastery services with educational cinema techniques can reduce the behaviour of academic procrastination of class VIII-B students at the Mts Muslimat NU Palangka Raya. The trial of the development of content mastery services with educational cinema techniques was obtained from the results of the Wilcoxon test statistic which showed a posttest value lower than the pretest value. The results of the statistical analysis of differences in academic procrastination behaviour after the pretest and posttest five that the Asyimp value. Sig. (2-tailed) Is 0.00. Because of Asyimp. Sig. <real level (α / 2 = 0.05) then Ho is rejected, and Ha is accepted. The model of content mastery services with effective educational cinema techniques can reduce students' academic procrastination behaviour. This conclusion is based on the comparison of the results of the pretest and posttest scores which showed a decrease in the students' academic procrastination behaviour before and after being given content mastery services with educational cinema techniques.